Biosocial spaces and neurocomputational governance: brain-based and brain-targeted technologies in education. Issue 2 (4th March 2018) - Williamson, Ben; Pykett, Jessica; Nemorin, Selena
ABSTRACT: Recently, technologies based on neuroscientific insights into brain function and structure have been promoted for application in education. The novel practices and environments produced by these technologies require new forms of 'biosocial' analysis to unpack their implications for education, learning and governance. This article provides an original analysis of current 'brain-based' R&D by the edu-business Pearson to apply artificial intelligence in education, and by the computing company IBM to develop cognitive systems for learning. These forms of neurocomputation are examined as technologies designed to function according to neuroscientific understandings of the brain, and to impress themselves on the cerebral lives of learners. The brain-based educational technologies proposed by Pearson and IBM are intended to optimize human cognition as a technique of human capital development in order to enhance the performance of education systems to secure a comparative advantage in a globalizing policy space, exemplifying new forms of neurocomputational governance and capital.